A four-way broadband filtering power divider with improved matching network for X-band application - Wang, Wensong (2021)
This study presents a novel design methodology of one-to-four filtering power divider (FPD) with a broadband response. It comprises three one-to-two power dividers (PDs) and a broadband bandpass filtering circuit in series. The impedance transformer of the one-to-two PD is designed into a dual-T-type symmetrical structure for improving the matching network and broadening the bandwidth, which includes a tapered transmission line, two cascaded microstrip lines with the same characteristic impedance, as well as a stepped-impedance open stub. The bandpass filtering circuit is formed by three coupled quarter-wavelength microstrip lines in parallel, where the intermediate subresonator is grounded via a hole instead of half wavelength line for pursuing a wider bandpass characteristic. The proposed FPD is fabricated and measured. The good performance is achieved with the return loss of >13.8 dB for input/output ports as well as minimum insertion loss of <0.21 dB (over the −6 dB splitting ratio) from 7.3 to 13 GHz.